Immune-Active Microenvironment in Small Cell Carcinoma of the Ovary, Hypercalcemic Type: Rationale for Immune Checkpoint Blockade. (22nd January 2018) - Jelinic, Petar; Ricca, Jacob; Van Oudenhove, Elke; Olvera, Narciso; Merghoub, Taha; Levine, Douglas A; Zamarin, Dmitriy
Abstract: Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT), is a highly aggressive monogenic cancer driven by SMARCA4 mutations. Here, we report responses to anti-PD1 immunotherapy in four patients and characterize the immune landscape of SCCOHT tumors using quantitative immunofluorescence and gene expression profiling. Unexpectedly for a low mutation burden cancer, the majority of the tumors (eight of 11 cases) demonstrated PD-L1 expression with strong associated T-cell infiltration ( R 2 = 0.60–0.95). PD-L1 expression was detected in both tumor and stromal cells, with macrophages being the most abundant PD-L1-positive cells in some tumors (three of 11 cases). Transcriptional profiling revealed increased expression of genes related to Th1 and cytotoxic cell function in PD-L1-high tumors, suggesting that PD-L1 acts as a pathway of adaptive immune resistance in SCCOHT. These findings suggest that although SCCOHT are low–mutational burden tumors, their immunogenic microenvironment resembles the landscape of tumors that respond well to treatment with PD-1/PD-L1 blockade.